2017
DOI: 10.15403/jgld.2014.1121.263.trs
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and Safety of Golimumab in Treating Outpatient Ulcerative Colitis: A Real-Life Prospective, Multicentre, Observational Study in Primary Inflammatory Bowel Diseases Centers

Abstract: Background & Aims: Golimumab (GOL) has been recently approved in Italy for the treatment of ulcerative colitis (UC) unresponsive to standard treatments. Our aims were to assess the real-life efficacy and safety of GOL in managing UC outpatients in Italian primary Inflammatory Bowel Diseases (IBD) centres.Methods: Consecutive UC outpatients with at least 3-months follow-up were enrolled. Primary end-point was the induction and maintenance of remission in UC, defined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 28 publications
(44 reference statements)
3
33
2
Order By: Relevance
“…reported a 12‐week CR rate (defined as Mayo score ≤2) of 44.1% and a 6‐month CR rate of 36.5% among 93 patients included in a multicenter study . In our study we found a 12‐week CR rate of 47%, comparable to the results of some (but not all) previously published reports. Of note, this lack of concordance may be explained by the different definitions of CR used by different authors.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…reported a 12‐week CR rate (defined as Mayo score ≤2) of 44.1% and a 6‐month CR rate of 36.5% among 93 patients included in a multicenter study . In our study we found a 12‐week CR rate of 47%, comparable to the results of some (but not all) previously published reports. Of note, this lack of concordance may be explained by the different definitions of CR used by different authors.…”
Section: Discussionsupporting
confidence: 89%
“…Reporting adverse events in previous real‐life experiences with golimumab was not homogenous across studies. Some did not report any adverse events, while others reported rates of adverse events requiring treatment discontinuation of 0%, 2.8%, 3.2% and 9%, respectively. In our series the overall adverse event rate was 10% over the whole study period, with 8% requiring the withdrawal of golimumab (Table ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations